The role of chemoradiation for patients with resectable or potentially resectable pancreatic cancer. Issue 4 (April 2012) - Kimple, Randall J; Russo, Suzanne; Monjazeb, Arta; Blackstock, A William
Conflicting data and substantial controversy exist regarding optimal adjuvant treatment for those patients with resectable or potentially resectable adenocarcinoma of the pancreas. Despite improvements in short-term surgical outcomes, the use of newer chemotherapeutic agents, development of targeted agents and more precise delivery of radiation, the 5-year survival rates for early-stage patients remains less than 25%. This article critically reviews the existing data for various adjuvant treatment approaches for patients with surgically resectable pancreatic cancer. Our review confirms that despite several randomized clinical trials, the optimal adjuvant treatment approach for these patients remains unclear.